2007
DOI: 10.1249/01.mss.0000247003.32589.a6
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Strength, Aerobic Fitness, and Metabolic Syndrome Risk in Flemish Adults

Abstract: Although cross-sectional, the present results support inclusion of strength training in addition to aerobic exercise in physical activity recommendations for women, because both types of activity might show additional effects in reducing the risk of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
2
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 28 publications
8
88
2
15
Order By: Relevance
“…The principal finding of this study was that both grip strength and abdominal adiposity are each independently associated with individual and clustered metabolic risk factors in women, but not in men (Table 3). Previous studies have indicated that muscular strength is a significant predictor of metabolic risk in adults (Sayer et al, 2007;Wijndaele et al, 2007). However, few studies have evaluated the independent importance of abdominal adiposity and fitness (Sayer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal finding of this study was that both grip strength and abdominal adiposity are each independently associated with individual and clustered metabolic risk factors in women, but not in men (Table 3). Previous studies have indicated that muscular strength is a significant predictor of metabolic risk in adults (Sayer et al, 2007;Wijndaele et al, 2007). However, few studies have evaluated the independent importance of abdominal adiposity and fitness (Sayer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have investigated the independent contribution of muscular strength and abdominal fat to individual and clustered metabolic risk factors. A recent study by Wijndaele et al (2007) has demonstrated that muscular strength is inversely related to a metabolic risk factor in women, even after adjustment for abdominal fat and other potential confounding factors. However, their studies have characterized abdominal fat by simple anthropometric measures such as waist circumference.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both in the elderly and the general population, muscle strength is inversely associated with allcause mortality, 1 osteoporosis, 2 cardiovascular diseases, 3 metabolic syndrome prevalence 4 and other pathological conditions and chronic diseases. 5 Heritability estimates vary from 31 to 78% with large differences between muscle groups, contraction velocities or muscle lengths (reviewed in Peeters et al 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the health benefits of physical activity can only be seen with regular practice, a positive relationship between regular physical activity and the reduction of the risk and improvement in MS-related risk factors is expected (Braith, Stewart, 2006;Li, Liu, Lin, 2006;Wannamethee, Shaper, Whincup, 2006;Lakka, Laaksonen, 2007;Wijndaele et al, 2007). On the other hand, it is well-known that sedentarism is a risk factor for the development of several degenerative diseases (ATPIII, 2001).…”
Section: Introductionmentioning
confidence: 99%